Penyuluhan Kesehatan Gigi dan Mulut di Kecamatan Minasatene Kabupaten Pangkajene Kepulauan - Palapessy, Victor E D; Abdullah, Dahlan; Prastyo, Eko; Nurhaedah, Nurhaedah; Tahulending, Anneke A; Andi Latif, Sarifudin; Erliana, Cut Ita (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Dental and oral health is the most important thing for human life and is part of general health. What society needs to pay attention to. To achieve optimal dental and oral health, regular maintenance must be carried out. Treatment can be started from paying attention to the food diet, limiting foods that contain sugar and sticky foods. Cleaning plaque and remaining food debris and brushing teeth must use techniques and methods that do not damage the tooth structure. The aim of the Dental and Oral Health PkM is to achieve changes in knowledge. Individual counseling methods are used to develop new behaviors, or to coach someone who is becoming interested in a behavior change or innovation. This individual approach is used because everyone has different problems or different reasons regarding the acceptance or new behavior. including: 1) Guidance and Counseling 2) Interviews (Interview). The expected result is an increase in understanding, attitude and skills that will change behavior towards healthy behavior and can carry out healthy behavior in daily life, especially regarding dental and oral health.